Job Performance: Modelling Human Resource Practices to Enhance Performance during Post-pandemic Covid-19 - MOHD AYUB KHAN, ANIS SURAYA (Research in Management of Technology and Business, 2023)
Malaysia has entered the endemic phase on April 1, 2022. However, employees had trouble in adjusting to work at office, after two years work at home. Their motivation is affected due to change of working environment. In order to prevent performance from declining, it is crucial to understand variables that can increase their job performance. The objective of this study is to identify the effect of compensation, training, and hybrid workplace on job performance. This study is quantitative research. 5-point Likert-scale questionnaire is used to collect data from the population of employees who is working in the financial sector in Selangor, with 384 sample size. The data is analyzed using SPSS software. However, only 118 data were collected. The results show that there is a significant positive effect of compensation, training, and hybrid workplace on job performance among employees. While conducting this study, the target for the respondents is limited to those who works in financial sector only in Selangor. This study is important for researchers to expand their understanding on the enhancement of job performance among employees in the financial sector in Selangor.